Deletion of the extracellular matrix glycoprotein ADAMTSL3 increases pro-fibrotic signalling and exacerbates heart failure in mice. (3rd October 2022) - Rypdal, K; Melleby, A O; Robinson, E L; Palmero, S; Seifert, D; Martin, D; Andreassen, K; Dahl, C P; Sjaastad, I; Toennessen, T; Stokke, M; Heymans, S; et al.
Abstract: Background/Introduction: Cardiac fibrosis is a central pathophysiological process accompanying most cardiac diseases including heart failure, and is a predictor of poor outcomes. The fibrotic process is mediated by activated cardiac fibroblasts (CFBs), so-called myofibroblasts, which produce excessive amounts of type I collagen and other ECM molecules. The ADAMTSL family of glycoproteins is upregulated in the cardiac extracellular matrix (ECM) during heart failure, but their function in the heart is unknown. Some ADAMTSL proteins are suggested to regulate the TGFβ, a major driver of myofibroblast activation and cardiac fibrosis. Purpose: The purpose of this study was to examine the role of ADAMTSL3 in TGFβ-regulation and heart failure. Methods: ADAMTSL3 expression was analysed in failing hearts of patients and mice. To study the functional role of ADAMTSL3 in the failing heart, an Adamtsl3 knock-out (L3-KO) mouse was generated, and WT and L3-KO littermates were subjected to experimental heart failure by aortic banding (AB), or sham surgery, for a total of six weeks. The mice were followed with echocardiography and MRI, and the left ventricles (LVs) were harvested one and six weeks after AB or sham surgery, with molecular analyses performed. To elucidate molecular functions of ADAMTSL3 in vitro, we overexpressed ADAMTSL3 in CFBs producing an extensive ECM. Results: We determined that ADAMTSL3 was produced by CFBs and upregulated in failing hearts of patients and mice. The L3-KO mice had a normal cardiac phenotype at baseline, but upon increased LV afterload developed a dilated cardiomyopathy phenotype with increased LV dilation and reduced systolic function from one week post-AB. Furthermore, high mortality was observed in the L3-KO mice post-AB, with 60% vs. 96% survival of WTs over six weeks. At one week post-AB RNA sequencing of LVs revealed 233 differentially expressed genes in L3-KO vs. WT, with Col1a1 and Postn among the most upregulated, suggesting increased fibrosis and TGFβ signalling. Increased canonical TGFβ signalling was confirmed by increased SMAD2/3 phosphorylation and increased Lox expression in L3-KOs six weeks post-AB. In vitro, ADAMTSL3 overexpression in cultured CFBs resulted in reduced collagen synthesis and reduced expression of COL1A1, LOX, CTGF and POSTN, indicating anti-fibrotic properties. Furthermore, ADAMTSL3 inhibited the expression of ACTA2 and SPP1, reduced α-SMA protein by 25%, and reduced proliferation and CFB contraction, suggesting attenuated TGFβ signalling and inhibited myofibroblast differentiation. Conclusions: ADAMTSL3 was upregulated in human and mouse heart failure, and served an anti-fibrotic and cardio-protective role in failing mouse hearts. Mechanistically, ADAMTSL3 was produced by CFBs and inhibited myofibroblast differentiation and collagen synthesis through TGFβ in cultured CFBs. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): The Research Council of Norway